1996
DOI: 10.1080/02827589609382935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season and urea treatment on infection of stumps of Picea abies by Heterobasidion annosum in stands on former arable land

Abstract: Between 1986 and 1990, a series of thinnings were made in previously unthinned first-rotation stands on former arable land located in the southern half of Sweden. The aim was to evaluate the effects of season and urea treatment on the frequency of infection of stumps of Norway spruce (Picea abies (L.) Karst.) by the root-rot fungus Heterobasidion annosum (Fr.) Bref. Untreated stumps, resulting from 60 thinnings (22-100 stumps each, altogether ca 3000 stumps) made at different times of year, were investigated 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 21 publications
1
61
1
Order By: Relevance
“…Consequently, adequate measures and correctly chosen tree species and management approaches depending on a certain forest site may substantially decrease possible wood losses caused by Heterobasidion spp. according to experience from Sweden and Lithuania (Vollbrecht et al 1995;Brandtberg et al 1996;Daniel et al 1998;Vasiliauskas, Stenlid 1998b;Wang et al 2014). Nevertheless, another vision in forest management approaches and in intensification of forest operations should be considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, adequate measures and correctly chosen tree species and management approaches depending on a certain forest site may substantially decrease possible wood losses caused by Heterobasidion spp. according to experience from Sweden and Lithuania (Vollbrecht et al 1995;Brandtberg et al 1996;Daniel et al 1998;Vasiliauskas, Stenlid 1998b;Wang et al 2014). Nevertheless, another vision in forest management approaches and in intensification of forest operations should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…The spores of Heterobasidion spp. penetrate into the Norway spruce fresh stumps (Rishbeth 1951) mainly, while the temperature is above 0°C (Brandtberg et al 1996). Thus, long-term changes in mean annual temperature as well as the mean number of days with positive temperature will make climatic conditions favourable for Heterobasidion spp.…”
Section: Discussionmentioning
confidence: 99%
“…Summertime loggings in Fennoscandia create fresh stumps susceptible to spore infection as the basidiospores are produced mainly during the summer months (Kallio, 1970;Brandtberg et al, 1996). Recent studies have shown that annual temperature sum cannot explain the spatial variation in the spore deposition (Kasanen et al, 2011;Witzell et al, 2011).…”
Section: Figurementioning
confidence: 99%
“…Since treatment of stumps with biological or chemical agents has been successful in preventing spore infection of stump surfaces (Korhonen et al 1994, Pratt 1994, Brandtberg et al 1996 and subsequent development of root rot, treatment of stumps at clear-felling may reduce the risk of infection in subsequent rotations. However, clearfelling operations may cause mechanical damage to stump roots, i.e.…”
Section: Introductionmentioning
confidence: 99%